Misdiagnosis of tuberculous infection as pseudo-bursa cyst after total hip arthroplasty: a case report - Zhen Jia; Zhengqi Chang; Shiyong Wan (Frontiers in Surgery)
This article reports and analyzes a case of postoperative tuberculosis infection in an 80-year-old female after total hip arthroplasty, which was misdiagnosed and mistreated due to imaging findings resembling a pseudo-bursa cyst. The patient had a history of right femoral neck fracture, underwent right total hip arthroplasty 4 years ago, and developed a lump on the posterior side of the right thigh 1 year ago. Initial MRI at another hospital diagnosed it as a pseudo-bursa cyst and underwent excision surgery, but recurred 2 months later. Upon admission, repeated fluid aspiration, biochemical analysis of the fluid (showing high protein, high specific gravity, and positive Rivalta test), PPD, and T-SPOT.TB tests all indicated active tuberculosis infection. Cheese-like necrosis and granuloma formation were found during surgery, confirming postoperative tuberculosis infection. The patient underwent local debridement surgery combined with 9 months of standard HRZE anti-tuberculosis treatment (isoniazid, rifampicin, pyrazinamide, and ethambutol). Follow-up at 9 months showed the lump had disappeared, inflammatory markers returned to normal, and the prosthetic joint remained stable with improved joint function. This case highlights the challenge of tuberculosis infection being masked by common postoperative complications, emphasizing the importance of multidimensional examination and comprehensive diagnosis of diseased tissues to reduce misdiagnosis rates, improve treatment success rates, and enhance patient quality of life.